URGENSI TERHADAP PELAKSANAAN INSOLVENCY TEST DALAM PENETAPAN STATUS PAILIT DI INDONESIA - Charina Putri Besila; Tazkya Salsabila; Shrishti Shrishti (PROSIDING SERINA, 2021)
The main purpose of bankruptcy law is to solve the problems of debtors whose assets are not sufficient to be able to pay their debts to creditors. The imposition of bankruptcy through debt proof in the concept of the Bankruptcy Law and Suspension of Debt Payment Obligations in fact cannot always be proven simply, because there are many other provisions that sometimes become problems in the imposition of bankruptcy, for example proving fictitious creditors, lawsuits against the board of directors that cause bankruptcy, and so on. This research discusses the urgency in terms of the implementation of insolvency tests in Indonesia to establish bankruptcy status for debtors. This study was conducted because researchers saw that there are still many debtors who can actually be said solven, but because of the absence of arrangements regarding insolvency test, the debtor was declared bankrupt without any chance of proof through insolvency test. This research aims to make readers understand the importance of the implementation of insolvency test in the determination of bankruptcy status. Data collection is done through library studies by looking for literature sources related to insolvency tests. The results of this study show that insolvency test is one of the important things to be presented in the regulation of bankruptcy law in Indonesia that can protect all parties, both creditors, debtors and even stakeholders.Tujuan utama dari hukum kepailitan adalah untuk menyelesaikan permasalahan debitor yang hartanya tidak cukup untuk dapat membayar utang-utangnya kepada kreditor. Penjatuhan pailit melalui pembuktian utang dalam konsep Undang Undang Kepailitan dan Penundaan Kewajiban Pembayaran Utang nyatanya tidak selalu dapat dibuktikan secara sederhana, karena banyaknya ketentuan lain yang terkadang menjadi permasalahan dalam penjatuhan pailit, misalnya pembuktian kreditur fiktif, gugatan kepada direksi yang menyebabkan kepailitan, dan lain-lain. Penelitian ini membahas mengenai apa urgensi dalam hal pelaksanaan insolvency test di Indonesia untuk menetapkan status pailit bagi debitur. Penelitian ini dilakukan karena peneliti melihat bahwa masih banyak debitur yang sejatinya bisa dikatakan solven, namun karena tidak adanya pengaturan mengenai insolvency test, debitur tersebut dinyatakan pailit tanpa adanya kesempatan pembuktian melalui insolvency test. Penelitian ini bertujuan agar pembaca memahami pentingnya pelaksanaan insolvency test dalam penetapan status pailit. Pengumpulan data dilakukan melalui studi pustaka dengan mencari sumber literatur yang berkaitan dengan insolvency test. Hasil penelitian ini menunjukkan bahwa insolvency test adalah salah satu hal yang penting untuk dihadirkan di regulasi hukum kepailitan di Indonesia yang dapat melindungi semua pihak, baik kreditur, debitur bahkan sampai stakeholder.